Chemical Alternatives Assessments 2013
DOI: 10.1039/9781849737234-00157
|View full text |Cite
|
Sign up to set email alerts
|

Hewlett‐Packard's Use of the GreenScreen™ for Safer Chemicals

Abstract: The electronics industry is now being impacted by a rapidly growing number of chemical regulations and substance restrictions. In the light of this trend, there is a significant risk of facing multiple substitutions for the same application unless potential replacement technologies are properly assessed against environmental and human health criteria in advance of their widespread adoption. To ensure that replacements for restricted substances have lower impact to human health and the environment, it is essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…Various industry sectors are using alternatives assessment tools during product development [16]. For example, Hewlett Packard uses GreenScreen® to assess the human health and environmental impacts of alternatives to chemicals restricted in the electronics industry [17].…”
Section: A Substitution and The Growing Role Of Alternatives Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Various industry sectors are using alternatives assessment tools during product development [16]. For example, Hewlett Packard uses GreenScreen® to assess the human health and environmental impacts of alternatives to chemicals restricted in the electronics industry [17].…”
Section: A Substitution and The Growing Role Of Alternatives Assessmentmentioning
confidence: 99%
“…• Streamlined approach to evaluating life-cycle impacts and exposure [54] • An alternatives assessment approach with clear triggers and checklists for exposure and LCA, and a harmonized approach among local jurisdictions to meet regulatory requirements [17] • Need for more models and case studies for alternatives assessment; for example, case studies that describe the use of tools and lessons learned (identified by multiple sources)…”
Section: Harmonization Of Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…When it comes to selecting what chemical(s) to use, the decision stakes can be high. For many product manufacturers, it is critical to minimize the number of times they have to replace a chemical of concern because these substitutions can be expensive and disrupt commercialization schedules (Holder, Mazurkiewicz, Robertson, & Wray, ). For many brands and retailers, the conversation with suppliers has shifted from piecemeal chemical substitution to making systematic evaluation of alternative formulations a “fundamental component of product design” (McFadden, ).…”
Section: Introductionmentioning
confidence: 99%
“…This might be especially important for AA, which is traditionally focused on choosing an alternative chemical that is less hazardous than the existing baseline chemical in a product (Heine & Whittaker, ; Holder et al, ). Once the less hazardous than baseline threshold is met, the evaluation considers more complex interactions among hazard and exposure reduction, as well as other attributes.…”
Section: Introductionmentioning
confidence: 99%